Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Hamada Tengan, Alessandra Eileen (2019)
The main aim of this dissertation is to propose a strategic plan for Camposol, which is one of the leading Peruvian export companies in the agribusiness sector agribusiness sector with a varied portfolio of fruits, vegetables and seafood. Based on the assumption that the year 2016 is current, the internal and external diagnosis was made, obtaining as a result that the organization has a strong internal and competitive position. However, in order to take advantage of their points in favor and minimize the impact of their elements against them, strategies were proposed to implement within which, in the corporate sphere, the related diversification of super grains such as chia and cacao, it is the best for the company at this moment. For this, both the redefinition of its strategic business units and the redesign of its structure are essential for the effective implementation of all the strategies proposed in the SWOT matrix. To conclude, key indicators have been proposed that contribute to the creation of company value and allow it to measure its results and performance.